Integrating Self-Care into Nursing Education and Practice: Strategies for Sustainable Wellbeing - Pras Ramluggun; David Morning (Education Sciences)
Self-care is a complex concept that incorporates various strategies designed to promote personal wellbeing and prevent illness, which is a critical need in nursing given the profession’s inherent stressors. The physical, emotional, spiritual, and psychological demands placed on nurses can significantly influence their wellbeing and the quality of care they provide. Yet, professional accountability and responsibility for self-care remains contested within the profession. To support a healthier and more sustainable healthcare workforce, Approved Education Institutions (AEIs) delivering pre-registration nursing programmes can play a pivotal role in embedding self-care ethos and practices into the nursing curricula. Grounded in educational psychology and drawing on insights from related theories, this paper explores barriers to self-care, proposes actionable interventions, and advocates for its integration as a cornerstone of nursing education.